β-catenin functions as a molecular adapter for disordered cBAF interactions - Chan, Yuen San; Gao, Qinyu; Robinson, Sarah A; Wang, Wenzhi; Filandrova, Ruzena; Weinhold, Lisa-Maria; Cabrera, Mario Loeza; Zhang, Miao; Ambati, Chandra Shekar R; Lerario, Antonio M; Putluri, Nagireddy; Kiseljak-Vassiliades, Katja; et al. (Molecular cell, 2025)
BAF (SWI/SNF) chromatin remodelers engage binding partners to generate site-specific DNA accessibility. However, the basis for interaction between BAF and divergent binding partners has remained unclear. Here, we tested the hypothesis that scaffold proteins augment BAF's binding repertoire by examining β-catenin (CTNNB1) and steroidogenic factor 1 (SF-1, NR5A1), a transcription factor central to steroid production in human cells. BAF inhibition rapidly opposed SF-1/β-catenin enhancer occupancy, impairing SF-1 target activation and SF-1/β-catenin autoregulation. These effects arise due to β-catenin's role as a molecular adapter between SF-1 and an intrinsically disordered region (IDR) of the canonical BAF (cBAF) subunit ARID1A. In contrast to exclusively IDR-driven mechanisms, adapter function is mediated by direct association of ARID1A with β-catenin's folded Armadillo repeats. β-catenin similarly linked cBAF to YAP1, SOX2, FOXO3, and CBP/p300, reflecting a general IDR-mediated mechanism for modular coordination between factors. Molecular visualization highlights β-catenin's adapter role for interaction of cBAF with binding partners.
Keywords: signální transdukce; Intrinsically Disordered Proteins; Signal Transduction; transkripční faktory p300-CBP; DNA-Binding Proteins; Forkhead Box Protein O3; Humans; fosfoproteiny; DNA vazebné proteiny; beta-katenin; adrenocortical carcinoma; scaffold proteins; Transcription Factors; Protein Binding; adaptorové proteiny signální transdukční; zesilovače transkripce; jaderné proteiny; vazebná místa; lidé; HEK293 Cells; Adaptor Proteins, Signal Transducing; Binding Sites; Steroidogenic Factor 1; transcription factors; unstructured protein; YAP-Signaling Proteins; vnitřně neuspořádané proteiny; chromatin remodeling; transcription regulators; HEK293 buňky; Nuclear Proteins; vazba proteinů; Enhancer Elements, Genetic; beta Catenin; protein FOXO3; p300-CBP Transcription Factors; steroid hormones; signální proteiny YAP; transkripční faktory; IDRs; co-activators; Phosphoproteins; steroidogenní faktor 1